NaGaS2: An Elusive Layered Compound with Dynamic Water Absorption and Wide‐Ranging Ion‐Exchange Properties. Issue 27 (28th April 2020) - Klepov, Vladislav V.; Berseneva, Anna A.; Pace, Kristen A.; Kocevski, Vancho; Sun, Mengqi; Qiu, Peng; Wang, Hui; Chen, Fanglin; Besmann, Theodore M.; zur Loye, Hans‐Conrad
Abstract: Most ternary sulfides belonging to the MGaS2 structure‐type have been known for many years and are well‐characterized. Surprisingly, there have been no reports of the NaGaS2 composition, which contains Na, a monovalent cation slightly larger in size than Li, found in LiGaS2, a compound known for its non‐linear optical properties. Now it is demonstrated for the first time that the unique reversible water absorption in NaGaS2 has resulted in its absence from previous reports owing to difficulties encountered when characterizing this compound by SC XRD. The layered structure of this compound coupled with uniquely easy migration of water molecules between the layers allows for ion exchange with 3d and 5f metal cations. Some cations, for example, Ni 2+, facilitate exfoliation of the layers, providing a facile synthetic route to a new class of 2D chalcogenide materials and furthermore demonstrating that NaGaS2 can readily uptake uranyl species from aqueous solutions. Abstract : Diamond in the rough : A unique reversible water absorption property of NaGaS2 made it a long unnoticed member of the AGaS2 family owing to difficulties of its characterization with SC XRD. Ion exchange with divalent cations results in exfoliation of this layered compound upon sonication, opening a venue for a new class of 2D materials.